Nahrwan Clays Study for Brick Industry (Baghdad Science Journal, 2008)
Nahrawan clay deposits lies in Diyala governorate , 65 Km, NE of Baghdad , according to the previous work in this field, in which they study the reserve belong to category of investigation ( C2 & C1 ) , we choice the proper area to investigation of category (B) with drill net( 200x 200m ) to rise the amount of reserve. The investigation work included drilling (116) boreholes of total depth ranges from (10.0-12.55m) , showed mainly clayey and silty deposits with little sand , and the typical borehole (648) represents all types of sediment in the area , and most of boreholes without sandy deposits , and all of these deposits is Quaternary sediment which is consist of two main sedimentary cycles ( the Pleistocene & Holocene ) .Chemical analysis for (343) samples were done , and physical test carried on ( 143 ) samples , and all show suitable properties for clay brick industry . the area of investigation covered ( 5.200.000 m2) involving ( 620.000 m2 ) containing soluble salt more than ( 3.5%) , which was separated from the total area , so the residual (4.580.000m2 ) had been taken to calculate the reserve , with depth of ( 10.76m) for the industrial clay bed . The reserve calculations depended on the following chemical & physical Properties: The chemical analysis shows that , CaO ( 16.53%) MgO ( 4.65% ) , SO3 ( 1.42%) , T.S.S. (2.42%) , the physical properties are unfired properties Which contains Bulk density ( 2.09gm/cm3) , moisture content (20.95%) , linear dry shri. (7.63%) , and fired properties which contain water absorption (18.8%) , linear shri. (0.8%) volume shri. (2.212% ) , compressive strength ( 468.606Kg/cm2) .So the reserve of category (B) is ( 49.280. 800 m3 ) or (102.966.000 Ton) the physical test showed that the brick classified into class (A-B) .